The investigation of xylazine, detomidine, isoflurane and sevoflurane anaesthetic combinations on clinical, laboratory and cardiovascular parameters and on intraocular pressure in horses - EROL, H.; ARICAN, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of this study was to investigate the effects of anaesthetic combinations of xylazine, detomidine, sevoflurane and isoflurane on clinical, laboratory, and cardiovascular parameters as well as their effects on intraocular pressure in horses. Twenty-four mixed-breed horses (twelve male and twelve female) were used for this study. The horses were allocated into four groups (six horses in each group): XS (xylazine-sevoflurane), XI (xylazine-isoflurane), DS (detomidine-sevoflurane) and DI (detomidine-isoflurane). Clinical evaluations, hematological, biochemical tests and measurement of intraocular pressure were done before (0th), during (5th, 15th and 30th min) and at the end of anaesthesia (60th min). The detected differences were statistically evaluated. In conclusion, this study shows that the anaesthetic combinations of sevoflurane and isoflurane with xylazine and detomidine provided safe and suitable anaesthesia in horses. Our study did not reveal any statistical differences in intraocular pressure measurements. However, it should be noted that intraocular pressures were measured with the animals lying down and our results do not rule out changes in intraocular pressures in a standing position. We concluded that these anaesthesia protocols are suitable for ophthalmic surgery.